CPR-related injuries after non-traumatic out-of-hospital cardiac arrest: Survivors versus non-survivors - Karasek, Jiri; Slezak, Jakub; Stefela, Radek; Topinka, Martin; Blankova, Alzbeta; Doubková, Alena; Pitasova, Tereza; Nahalka, David; Bartes, Tomas; Hladik, Jiri; Adamek, Tomas; Jirasek, Tomas; et al. (Resuscitation, 2022)
AIM: There have been no direct comparisons of cardiopulmonary resuscitation (CPR)-related injuries between those who die during CPR and those who survive to intensive care unit (ICU) admission. This study aimed to compare the incidence, severity, and impact on survival rate of these injuries and potential influencing factors. METHOD: This retrospective multicenter study analyzed autopsy reports of patients who experienced out-of-hospital cardiac arrest (OHCA) and were not admitted to hospital. CPR-related injuries were compared to OHCA patients with clinical suspicion of CPR-related injury confirmed on imaging when admitted to the ICU. RESULTS: A total of 859 out-of-hospital cardiac arrests (OHCA) were divided into 2 groups: those who died during CPR and underwent autopsy (DEAD [n = 628]); and those who experienced return of spontaneous circulation and admitted to the ICU (ICU [n = 231]). Multivariable analyses revealed that independent factors of 30-day mortality included no bystander arrest, cardiac etiology, no shockable rhythm, and CPR-related injury. Trauma was independently associated with older age, bystander CPR, cardiac etiology, duration of CPR, and no defibrillation. CPR-related injury occurred in 30 (13%) patients in the ICU group and 547 (87%) in the DEAD group (p < 0.0001). Comparison of injuries revealed that those in the DEAD group experienced more thoracic injuries, rib(s) and sternal fractures, and fewer liver injuries compared to those in the ICU group, without differences in injury severity. CONCLUSION: CPR-related injuries were observed more frequently in those who died compared with those who survived to ICU admission. Injury was an independent factor of 30-day mortality.
Keywords: urgentní zdravotnické služby; Cardiopulmonary Resuscitation; Out-of-Hospital Cardiac Arrest; Survivors; retrospektivní studie; lidé; kardiopulmonální resuscitace; přežívající; Retrospective Studies; Emergency Medical Services; zástava srdce mimo nemocnici; Humans